Study of Moisture Absorption by Ranitidine Hydrochloride: Effect of % RH, Excipients, Dosage Forms and Packing Materials (Dhaka University Journal of Pharmaceutical Sciences, 2008)
Moisture absorption by ranitidine at three different level of relative humidity (RH) has been studied. Percentage of moisture absorption at 22%, 57% and 75% RH was 0.6%, 3.1%, and 4.9% respectively. Ranitidine blended with various excipients (maize starch, lactose, avicel PH-101, mannitol, povidone K-30, magnesium stearate and purified talc) were also exposed to 75% relative humidity (% RH) to observe their effects on moisture absorption. Moisture absorption by ranitidine was either increased or decreased when ranitidine was mixed with various diluents, binders and lubricants. Ranitidine mixed with lactose, aerosil-200 and avicel PH-101 absorbed minimum amount of moisture while ranitidine mixed with maize starch absorbed maximum. On the other hand, ranitidine mixed with mannitol was found to absorb intermediate amount of moisture. Ranitidine mixed with povidone K-30 absorbed almost double moisture than pure ranitidine. Ranitidine mixed with purified talc and magnesium stearate absorbed almost same amount of moisture. The type of dosage form and type of packing materials also influenced moisture absorption. Uncoated tablets absorbed maximum amount of moisture (4.5%) while coated tablets absorbed minimum (2%). On the other hand, capsule was found to absorb intermediate amount of moisture (3.4%). PVC-Alu foil packed uncoated ranitidine tablet absorbed more moisture (3.3%) than that of Alu-Alu packed uncoated ranitidine tablet (0.16%). Key words: % RH, ranitidine hydrochloride, moisture, absorption Â DOI = 10.3329/dujps.v7i1.1219 Dhaka Univ. J. Pharm. Sci. 7(1): 59-64, 2008 (June)